Alat Pengatur Takaran Pakan Ikan Otomatis menggunakan metoda fuzzy dengan sensor suhu dan pH - Anton Hidayat (Elektron : Jurnal Ilmiah, 2020)
Busy activities such as work, out of town, holidays with family make it difficult to feed fish done well because farmers can not always be near the pond. In addition to the erratic weather that can reduce the quality of pond water so that the dose of feed must be adjusted again from the normal dose. Fish feed can be done automatically by making feeder equipment scheduled and measured using RTC, keypad and LCD as an interface with the user. And measured using a screw rotation and encoder in order to know the number of thread rotation is done. After testing, it was found that this tool can provide fish feed on schedule with an average dose of 302.6 g per 100 thread turns with a lot of feed errors coming out by 1.03% in an interval of 5.77 seconds.